Maternal-neonatal listeriosis - Charlier, Caroline (Virulence, 2020)
Listeriosis is a rare and severe foodborne infection caused by Listeria monocytogenes. It manifests as septicemia, neurolisteriosis, and maternal-fetal infection. In pregnancy, it may cause maternal fever, premature delivery, fetal loss, neonatal systemic and central nervous system infections. Maternal listeriosis is mostly reported during the 2nd and 3rd trimester of pregnancy, as sporadic cases or in the context of outbreaks. Strains belonging to clonal complexes 1, 4 and 6, referred to as hypervirulent, are the most associated to maternal-neonatal infections. Here we review the clinical, pathophysiological, and microbiological features of maternal-neonatal listeriosis.